PENGARUH PEMAHAMAN SISWA DAN SISTEM PENILAIAN TERHADAP KETRAMPILAN BERBAHASA INGGRIS SISWA KELAS VI SD YAYASAN PENDIDIKAN JAYAWIJAYA KUALA KENCANA - Kho, Ronaldo; Quamilla, Vini; Ardiasih, Lidwina Sri (Jurnal SORA - Pernik Studi Bahasa Asing, 2023)
English lessons at SD Yayasan Pendidikan Jayawijaya are introduced to students starting from grade I. The sixth-grade student feels they are skilled in speaking, listening, reading, and writing in English. But in reality, many students are having difficulties with English. When the researcher came into the English class, many students said that were not confident in speaking English. This study aimed to determine whether understanding ability and assessment systems will influence speaking, listening, reading, and writing skills in English. This research was conducted on sixth-grade students of Sekolah Yayasan Pendidikan Jayawijaya with a population of 65, using ex post facto research. The measurement of variables using a Likert Scale with multiple regression analysis. The instruments used are two tests, a questionnaire, and observation. The results of the analysis show that the variables of speaking, listening, reading, and writing skills in English are influenced by the ability to understand. The assessment system has the least influence.